The Long and Winding Path to Private Financing and Regulation of Toll Roads - Estache, Antonio (World Bank, Washington, DC, 2015)
Road transport has long been the dominant form of transport for freight and passenger movement throughout the world. Because most road projects require investments with long amortization periods and because many projects do not generate enough demand to become self-financing through some type of user fee or toll, the road sector remains in the hands of the public sector to a much greater extent than other transport activities. But governments throughout the world, including those of many poor African and South Asian countries, are commercializing their operations to cut costs, improve user orientation, and increase sector-specific revenue. There seems to be demand for toll roads in specific settings, but the problems met by many of this "first generation" of road concessions-from Mexico to Thailand-have given toll projects a bad reputation. Many mistakes were made, and tolling is obviously not the best solution for every road. Most of the alternatives aim at improving efficiency (lowering costs). But there are many ways of getting the private sector involved in toll roads, thus reducing public sector financing requirements for the sector. Understanding the context in which toll roads are viable is essential both for their initial success and for effective long-run regulation. The authors provide a broad overview of issues at stake from the viewpoint of both privatization teams and regulators responsible for supervising contractual commitments of private operators and the government, to each other and to users.